Correlation of Assessment Scores and Performance of Students from Admission to Graduation at Liaquat College of Medicine and Dentistry - Faiza Siddiqui; Naila Baig; Zeelaf Shahid; Hanan Furqan Siddiqui; Mohd Subhan Ali Siddiqui (Journal of University Medical & Dental College, 2024)
BACKGROUND &OBJECTIVE: Gaining admission to medical school is highly competitive, requiring rigorous selection criteria by educational institutions. They carefully assess entry qualifications and eligibility tests to identify suitable applicants for their medical programs. The objective is to evaluate how well these criteria predict student's overall academic performance in medical colleges across Pakistan.METHODOLOGY: The descriptive, observational study was conducted at a private medical and dental College, in Karachi. A multiple linear regression analysis was conducted to predict the final year score based on factors such as HSC score, entry test score, and scores from the first, second, third, and fourth years.RESULTS: The study shows that the pre-medical scores of HSC and A levels have a moderate positive correlation with the first-year MBBS (r=0.403) and a strong correlation with the final-year scores (r=0.603). The entry test (MDCAT) has a moderately positive correlation with the first, third (r=0.348), and fourth-year (r=0.367) scores. On comparing pre-clinical year scores with clinical years, a strong positive correlation was seen between 1st year and 3rd year (r=0.721), 1st year and 4th year (r=0.570), 1st year and final year (r=0.619), 3rd year and 4th year (r=0.711), 3rd year and 5th-year scores (r=0.602), 4th year, and 5th-year scores (r=0.651).CONCLUSION: This study shows that the pre-medical scores and medical college entry tests can predict student’s overall future academic performance in professional examinations. Also, provides insight to medical educationists to identify weak students in their early medical college years.